The Impact of Smartphone Use on Student Behavior a Vocational Senior High School in Tangerang City, Indonesia - Eva Marsepa; Rizki Isfahan; Yuni Susilowati (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
The use of smartphones has reached all levels of society in Indonesia. It is necessary for parents to supervise smartphone use at home and for teachers to supervise smartphone use at school for the sake of students' development both at home and at school. Incorrect use of smartphones can have a negative impact on student behavior. This study aims to investigate the impact of smartphone use among students a Vocational Senior High School in Tangerang City, Indonesia. The research questions are: What are the reasons for smartphone use, and how does smartphone use affect student behavior at school? This study employs a descriptive qualitative method. Data collection techniques in this study include observation, interviews, and documentation. The results of the study indicate that students use smartphones for entertainment at school, such as playing offline or online games, watching videos obtained from friends, taking photos with friends, completing group assignments assigned by teachers, searching for answers while doing assignments, and searching for answers during exams or quizzes. The apps that students use a lot at school are Free Fire, YouTube, TikTok, Instagram, Google, WhatsApp, AI, and ChatGPT. Students' social behavior changes when they're busy with their smartphones. When students are given smartphones during class, they don't listen to the teacher and are busy with their phones. When it's break time, students follow the moves in the videos on their smartphones, which affects their behavior at school.